Fabrication of AChE/SnO2-cMWCNTs/Cu Nanocomposite-Based Sensor Electrode for Detection of Methyl Parathion in Water - Vikas Dhull (International Journal of Analytical Chemistry)
The work highlights inhibition-based Acetylcholinesterase (AChE) fabrication using composite nanomaterial comprising tin oxide nanoparticles (SnO2) and carboxylated multiwalled carbon nanotubes (cMWCNTs) for detection of pesticide methyl parathion (MP) in water samples. Working electrode AChE/SnO2-cMWCNTs/Cu exhibited high sensitivity with a linearity range of 1.0 μM to 160 μM and a minimum detection limit of 0.1 μM for MP in water. The fabricated electrode was found biocompatible and nontoxic which can be used to detect low concentrations of pesticide in water samples. The synergistic and facilitated electron transferring properties of SnO2-cMWCNTs/Cu made it an excellent support for immobilization of enzyme in sensing technology. The enzyme AChE was covalently immobilized with cMWCNTs using glutaraldehyde as crosslinking agent which has enhanced the storage stability and reusability of the method. The reusability attained was 30 times for 40 days when AChE/SnO2-cMWCNTs/Cu was stored at low temperature of 4°C. Developed sensor showed excellent analytical recovery of pesticide in water sample with negligible effect of interfering species. Also, AChE/SnO2-cMWCNTs/Cu was easily reactivated simply by varying pH of phosphate buffer. This method is fast, reliable, and accurate showing successful development of amperometric biosensor for detection of MP in water sample.